Double Guided Surgery in All-on-4® Concept: When Ostectomy Is Needed - Gabriele Tonellini; Raquel Saez Vigo; Giorgio Novelli (International Journal of Dentistry)
Background. The rehabilitation of edentulous jaws with guided and flapless surgery applied to the All-on-4 concepts is a predictable treatment with a high implant and prosthetic survival rates, but there are several contraindications for this technique like when bone reduction is needed due to a high smile line in the maxilla or when there is an irregular or thin bone crest. Purpose. To report a technique with double guided surgery for bone reduction and implant placement with the All-on-4 concept. Materials and Methods. 7 patients were included in the study. Guided implant planning was performed using CBCT, and the virtual templates were created with three dedicated software. Custom surgical templates were made for the ostectomy and for implants positioning. Results. 28 implants were placed using a double bone-supported surgical guide. The mean angular errors between the preoperative-planned implant and the postoperative-placed implant were 2.155° ± 2.03°; the mean distance errors between the planned and the placed implants were 0.763 mm ± 0.55 mm on the shoulder implant and 0.570 mm ± 0.40 mm on the apex implant. Conclusions. The results of our study indicate that this treatment is predictable with an excellent survival rate allowing excellent results even when bone reduction is mandatory.